2000
DOI: 10.1007/s004360050010
|View full text |Cite
|
Sign up to set email alerts
|

Restriction-fragment-length polymorphism analysis of small-subunit rRNA genes of Blastocystis hominis isolates from geographically diverse human hosts

Abstract: Genomic diversity among 14 isolates of Blastocystis hominis from 4 different geographic locations was examined by small-subunit rRNA (ssu rRNA) restriction-fragment-length polymorphisms (RFLP) using 5 different restriction endonucleases. On the basis of the observed RFLP patterns among the isolates, a total of 12 genotypes were identified, with 7 isolates exhibiting mixed RFLP genotypes. There was no correlation between B. hominis geographic origin and RFLP banding pattern or genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 28 publications
3
25
1
3
Order By: Relevance
“…Many epidemiologic studies reported only further use of molecular analysis if there are samples positive by culture. 4,17,24,[28][29][30] An obvious conclusion is that these studies did not provide a true representation of the prevalence of Blastocystis infections in human population studies where some culture systems used may not enable certain strains of Blastocystis to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiologic studies reported only further use of molecular analysis if there are samples positive by culture. 4,17,24,[28][29][30] An obvious conclusion is that these studies did not provide a true representation of the prevalence of Blastocystis infections in human population studies where some culture systems used may not enable certain strains of Blastocystis to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic characterization of Blastocystis from humans and animals was determined by an RFLP analysis of partial ssu rDNA (4). Although a few different primer pairs were used for the PCR-RFLP analysis of this gene in recent reports (3,7,12,19), we chose a primer pair specific to partial ssu rDNA of B. hominis (3) since mixed infection with intestinal protozoa might be found in some specimens. Genomic DNA and a primer pair (forward, 5Ј-G GAGGTAGTGACAATAAATC-3Ј; reverse, 5Ј-CGTTCATGATGAACAATT-3Ј) were used in PCR with conditions as described by .…”
Section: Methodsmentioning
confidence: 99%
“…possible coinfection with other microbes, and the possibility that what is now called B. hominis includes both pathogenic and nonpathogenic species or strains (9,14). Although we could not resolve the long-standing controversy about the pathogenicity of B. hominis, we urge caution in attributing symptomatology to B. hominis infection.…”
Section: Discussionmentioning
confidence: 88%
“…Although we did not design our study to address the controversial question of whether B. hominis is a pathogen (9,14,15,17,20,26,27,31,32), we took advantage of the high incidence of B. hominis infection by comparing the patterns of acquisition and excretion of B. hominis with those of the known pathogens and nonpathogens. We were intrigued to note that, in several respects, B. hominis behaved more like a nonpathogen than a pathogen.…”
Section: Discussionmentioning
confidence: 99%